Impact of Incident Parkinson's Disease on Satisfaction With Life - Buczak-Stec, Elzbieta W.; König, Hans-Helmut; Hajek, André (Frontiers in Neurology, 2018)
Aim: The aim of the study was to investigate the effect of the onset of Parkinson’s disease on life satisfaction. Method: Data from 2008, 2011 and 2014 were used from a population-based prospective cohort (German Ageing Survey; 8,982 observations in FE regression analysis) of community-residing individuals in the second half of life (≥ 40 years) in Germany. Satisfaction with life was quantified using the established Satisfaction with Life Scale. Physician-diagnosed Parkinson was reported. Results: In total, 48.9% were female. The mean age was 63.8 years (±11.3 years). Average life satisfaction equaled 3.8 (±0.7). Linear fixed effects regressions revealed that the onset of PD was associated with a considerable decline in life satisfaction (β=-.37, 95% CI -.69 to -.05, p<.05). This effect was significantly more pronounced in men. Moreover, a decrease in life satisfaction was associated with younger age, changes from ‘employed’ to ‘not employed’, worsening self-rated health, the onset of depression, and an increase in the number of physical illnesses. Conclusions: The onset of PD is associated with a marked reduction of life satisfaction among individuals in the second half of life in the total sample and in men, but not in women. For example, this effect was about twice as large as the effect of depression on life satisfaction. Moreover, the effect of PD on life satisfaction was more pronounced than the effect of a strong decrease in self-rated health (from ‘very good’ to ‘very bad’) on life satisfaction. Effective treatment of symptoms might contribute to maintaining life satisfaction.